1993
DOI: 10.1111/j.1526-4610.1993.hed3307385.x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine Without Aura and Reproductive Life Events: A Clinical Epidemiological Study in 1300 Women

Abstract: A retrospective study was conducted on 1300 women suffering from migraine without aura referred to the Headache Centers of Parma and Pavia from 1984 to 1990. All the data concerning their reproductive life, and the modifications induced by it on the course of headache were obtained from record-charts. Migraine frequently started at menarche (10.7%); in 60% of cases the migraine attacks occurred mostly or exclusively in the perimenstrual period, in 67% of cases disappeared during pregnancy, and in 24.1% signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
206
2
6

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(230 citation statements)
references
References 8 publications
16
206
2
6
Order By: Relevance
“…The above cited definitions for menstrual migraines were applied in this study. Classic population studies 5 demonstrate that menstru ation triggers off migraine in only 24% and tensional headaches in 39%, results very close to those obtained by this present study.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The above cited definitions for menstrual migraines were applied in this study. Classic population studies 5 demonstrate that menstru ation triggers off migraine in only 24% and tensional headaches in 39%, results very close to those obtained by this present study.…”
Section: Discussionsupporting
confidence: 81%
“…Majority of the epidemiological studies 1 -4 , 6 , 7 , 1 0 demonstrate that pregnant women with headaches prior to pregnancy re p o rt an impro v e m e n t in 55 to 90% of the cases, while in a smaller contingent of pregnant women, there is an onset of headaches during pregnancy 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, in a smaller contingent of pregnant women, there is an onset of headaches during pregnancy [7]; in our study, we found this phenomenon in 155/755 (21 %) of the women. However, some of these cases may have been caused by secondary headaches, in particular those linked to hypertensive disorders [5,8].…”
Section: Discussioncontrasting
confidence: 71%
“…6 Perimenstrual migraines are problematic as they last significantly longer, are more disabling, and are more difficult to treat pharmacologically than nonmenstrual migraines. 3,7,8 The definition of a menstrual period is two or more consecutive days of bleeding. 1 The IHS classifies menstrual migraine attacks as those that occur anytime from 2 days before onset to the last day of menses; the peak time for migraine attacks is between 2 days pre-menses and the first 2 days of the cycle.…”
mentioning
confidence: 99%